ARTISTIC INTERPRETATION OF HUMAN VIRTUES IN "TURKISH GULISTAN OR MORALITY" ABDULLA AVLONI - Egamova Shahida Jalilovna; Inomaliyeva Zilola Furkat kizi; Inomaliyeva Pokiza Furkat kizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines the educational value of Abdullah Avloni’s work "Turkish Gulistan or Morality" and the artistic interpretation of the human qualities reflected in it.